Accelerator-Driven System Analysis by Using Different Nuclear Data Libraries - T. Sugawara; Ts. Zolbadral; K. Nishihara; K. Tsujimoto (Atom Indonesia, 2012)
An accelerator-driven system (ADS) has been investigated to transmute minor actinide (MA) included in high-level waste. In the neutronic design of the ADS, the accuracy of nuclear data for MA and lead bismuth (LBE) which is the candidate material for coolant and spallation target, is important. To know the current accuracy of nuclear data libraries, this study aims to compare representative nuclear data libraries, JENDL-4.0, 3.3, ENDF/B-VII.1 and VII.0 through the neutronic calculation of the ADS geometry proposed as the IAEA benchmark problem. The calculation results showed that about 1.1%dk, 0.7%dk and 2.7%dk differences were observed between JENDL-4.0 and ENDF/B-VII.1, ENDF/B-VII.0 and JENDL-3.3 at the beginning of cycle, respectively. These results mean that the current nuclear data libraries are still insufficient for the neutronic design of the ADS. The enhancement of nuclear data libraries by cross section measurement is required and, moreover, integral experiments with MA and LBE isotopes are essential. Received: 29 June 2012; Revised: 22 August 2012; Accepted: 30 August 2012